Ipecacuahana induced emesis in the treatment of self-poisoned adults. Issue 4 (December 1985) - Gordon, G
Abstract : One hundred consecutive adult patients presenting to an Accident and Emergency Department following intentional self-poisoning were given 50 to 80 ml Paediatric Ipecacuahana Emetic Mixture BP as an emetic, together with two or three glasses of strong orange juice. A satisfactory emetic result was obtained in 99 patients. No toxic effects were noted in these patients, or in the one patient in whom emesis did not occur, and who subsequently refused gastric lavage. The potential toxicity of Ipecacuahana Syrup itself is discussed, and attention drawn to the lower Emetine content of Paediatric Ipecacuahana Emetic Mixture (BP), rather than that of the formulations used in previously published reports. The use of Paediatric Ipecacuahana Emetic Mixture B.P. in adults is effective and safe in this dosage.